Forced Alternative: Making Multigrade Schools Work For Children in Need in Rural Areas - Abregana, Betty C.; Oracion, Enrique G.; Mascuñana, Rolando (Silliman Journal, 2022)
This case study was conducted in two elementary schools of Negros Oriental to examine the situation of multigrade schools assisted by the Unicef In particular, it aims to assess the opportunities offered by the llama a,, well as identify the challenges associated with the teaching of iiiiiltraels daises. A multigrade school assigns to one teacher two or three grade lasts a way of meeting the educational needs of schoolchildren in far-oi, I q conformities where there are not enough teachers because of budget-er, itouraints. Through this mechanism, the government's thrust of "edu-WON fir alt" is operationalized. In Negros Oriental, almost one half 41%) of elementary schools are combined or multigrade schools. Even failft the combined or multigrade schools, more than half (57 %) are INNIfithit schools, Yet, without the multigrade schools, basic education mkt have remained beyond the reach of a big number of elementary 44001 qe children in the province, especially in remote barangays. Among other observations, this case study shows that the proper ieheistration of multigrade schools can be a workable alternative to Moiling the educational needs of children in the uplands and the coun-Avid.. Teacher training, improved school facilities and equipment, ad-iiiiitrative assistance, LGU support, and community participation con-trkil to making multigrade schools work for children in need. The ilfrikation of innovative teaching strategies enables teachers to be effec-Oki ist handling multigrade classes and sustains children's interest to 6" However, the study also shows that there is a continuing need for FOROOding our elementary school teachers to provide them skills to respond MON realities of a school setting in outlying communities.